Results and Elasticity of Gamification in Training and Development Processes - Santos, Siméia Azevedo (2021)
Gamification is the use of games elements in different contexts out of the games. It is a tool with potential application in several areas in management, like marketing and human resources, including training and development. Departing from this reference, this study has objective to identify the perception of efficiency and the measurable results in the gamification processes in training and development in a sample of the Brazilian market. This research is divided into two samples. The quantitative sample investigated the perception of efficiency of the professionals who already participated in the gamified training, the information was collected through an online form with Likert scale responses and treated with Minitab statistical software. The other sample was qualitative and sought to identify the perception of the professionals who developed the gamified training, and the results were submitted to the content analysis technique. The compiled results confirmed the presence of engagement and its influence on motivation as one of the advantage points for the application of gamification in training. It was also possible to find in these results the relevance of the design for the game / training interaction to work effectively. Among the trends of higher incidence found in this research are the possibility of associating gamification with virtual reality and augmented reality to enhance the experience lived by the player during training. As a secondary’s incidents, but also relevant and congruent with market trends, are the incidents of concision with relevance, interaction, applicability and the digital trail, items present in the concept of learning in micro-moments.